Evaluation of the effectiveness and safety of a genetically modified live vaccine in broilers challenged with Salmonella Heidelberg. Issue 6 (2nd November 2017) - Muniz, Eduardo Correa; Verdi, Renato; Leão, Joice Aparecida; Back, Alberto; Nascimento, Vladimir Pinheiro do
ABSTRACT: Salmonellosis ranks among the major diseases of commercial poultry, and its presence in poultry flocks is responsible for economic losses and risks related to public health. Vaccines are an important tool within integrated programmes to control salmonellosis. The purpose of this study was to assess cross-protection provided by the Poulvac® ST vaccine in the control of Salmonella Heidelberg in experimentally challenged 3- and 21-day-old birds. Eighty birds were identified and separated into four treatments (T1: vaccinated and challenged at 3 days of age, T2: unvaccinated and challenged at 3 days of age, T3: vaccinated and challenged at 21 days of age, and T4: unvaccinated and challenged at 21 days of age). The inoculum was produced from a Brazilian field strain of SH. At the end of the experiment, caecum and liver/spleen samples were collected for quantitative and qualitative analysis of SH, respectively. Analysis of the liver/spleen showed that Poulvac® ST significantly ( P  ≤   0.05) reduced the percentage of SH positivity in the group challenged at 3 days of age, while in the group challenged at 21 days this difference was almost considered significant ( P  = 0.1818). On the other hand, there was no statistically significant difference in SH count in the caecum (CFU/g) in the group challenged at 3 days, but for the group challenged at 21 days the SH counts were significantly ( P  ≤   0.05) lower in the vaccinated group when compared to the positive control.